2019
DOI: 10.1038/s12276-019-0263-x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin II negatively regulates BMP2-induced osteoblast differentiation and bone formation via PP2A Cα-mediated Smad1/5/9 dephosphorylation

Abstract: Peroxiredoxin II (Prx II), an antioxidant enzyme in the Prx family, reduces oxidative stress by decreasing the intracellular ROS levels. Osteoblast differentiation is promoted by bone morphogenetic protein 2 (BMP2), which upregulates the expression of osteoblast differentiation marker genes, through Smad1/5/9 phosphorylation. We found that Prx II expression was increased by a high dose of lipopolysaccharide (LPS) but was not increased by a low dose of LPS. Prx II itself caused a decrease in the osteogenic gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…BMPs belong to the TGF-β super-family, which are recognized as playing critical roles in regulating bone formation and proliferation 50,51 , as well as in angiogenesis 52,53 . However, some members of BMPs can commit MSCs to osteoblast lineages, such BMP2, BMP4, BMP6, and BMP7 54,55 . In a recent study, we reported that BMP9 (also termed as growth differentiation factor 2) is one of the most potent BMPs among the 14 types of BMPs in the induction of osteogenic differentiation 19,56 .…”
Section: Discussionmentioning
confidence: 99%
“…BMPs belong to the TGF-β super-family, which are recognized as playing critical roles in regulating bone formation and proliferation 50,51 , as well as in angiogenesis 52,53 . However, some members of BMPs can commit MSCs to osteoblast lineages, such BMP2, BMP4, BMP6, and BMP7 54,55 . In a recent study, we reported that BMP9 (also termed as growth differentiation factor 2) is one of the most potent BMPs among the 14 types of BMPs in the induction of osteogenic differentiation 19,56 .…”
Section: Discussionmentioning
confidence: 99%
“…PRDX2 is expressed in all cell types and is the third most abundant protein in erythrocytes [44]. Three PRDX isoforms (PRDX1, PRDX2, and PRDX6) are expressed in mature erythrocytes and PRDX2 is the most abundant protein among them [45]. The role of PRDX2 in protecting erythrocytes against oxidative stress has been verified by several studies using the same Prdx2-knockout mouse model [46][47][48][49][50][51][52][53][54][55].…”
Section: Erythrocytesmentioning
confidence: 89%
“…Prdx2 −/− have higher levels of bone mass than those of wild-type mice because PRDX2 is a negative regulator of BMP2-induced osteoblast differentiation [45]. PRDX2 also functions as a negative regulator of LPS-induced osteoclastogenesis and bone loss, which are induced by ROS-mediated JNK and STAT3 activation [71].…”
Section: Bonementioning
confidence: 99%
“…BMP2 is the only growth factor inducing the mesenchymal cells to differentiate into bone tissues. In the early stage of bone formation, BMP2 can not only recruit undifferentiated mesenchymal cells into bone formation to differentiate into bone cells, but also reverse the differentiation of fibroblast myoblasts and bone marrow basal cells into bone cells [14].…”
Section: Discussionmentioning
confidence: 99%